Barriers to perinatal mental health care experiences by midwives and obstetricians and their patients: A rapid review. (February 2023) - Marshman, Alixandria; Saunders, Emily; Chaves, Debbie; Morton Ninomiya, Melody E.
Highlights: Mental health care is essential during the perinatal period. Obstetricians and midwives are best positioned to observe the need for mental health. There are individual, institutional and societal barriers to perinatal mental health care. There are no differences in mental health barriers between midwifery and obstetrician patients. Addressing societal stigma is key to reducing stigma at all other levels. Abstract: Introduction: While perinatal mental health concerns are common, little attention is paid to noticing or addressing these concerns. Midwives and obstetricians are uniquely positioned to universally screen their patients for mental health conditions during the perinatal period, and provide referrals for additional mental health supports if relevant. Previous studies on perinatal mental health care have focused primarily on midwifery care, excluding perinatal healthcare providers such as obstetricians. This rapid review aims to examine the barriers to accessing mental health care during the perinatal period as experienced by obstetricians, midwives, and their patients. Methods: A rapid review of literature was conducted on barriers to perinatal mental health care as experienced by patients, midwives, and obstetricians. The search strategy included published literature from PubMed, CINAHL, PsycINFO, and Web of Science published between 2000 and 2020. All documents were screened by two researchers and disagreements were resolved through consensus with a third reviewer. After data from all included articles were extracted, thematic analysis was conducted, and findings were compared with related reviews that focused on mental health access for individuals who accessed midwifery care. Results: Of the 539 references and documents that were screened, 31 articles met the inclusion criteria. In the extraction phase, country, study objective(s), study design, perspective(s), barriers, and the dimension(s) impacted along the pathway to accessing care were retrieved from the 31 included articles. After all barriers were classified using the Supply-Side Dimensions of Access, we developed a classification framework to further examine stigma at the societal, institutional, and individual levels. Discussion: While midwives utilize a more holistic approach to care as compared with obstetricians, the barriers identified through this rapid review indicate that obstetricians and their patients face similar struggles to accessing and providing mental health care. Moreover, stigma plays a large role in the barriers experienced by patients, midwives, and obstetricians - at individual and institutional levels. Conclusion: Obstetricians encounter similar stigma-related barriers as midwives in detecting mental health concerns, as well as connecting clients to available mental health resources and supports. Therefore, to effectively eliminate barriers to accessing perinatal mental health care, a systemic change must be enacted throughout all three layers to address the deep-rooted stigma associated with accessing mental health care during the perinatal period.